Everyday ethics : inspired solutions to real-life dilemmas - Halberstam, Joshua (Penguin Books, 1993)
Focusing on personal ethics, this book explores the challenges we face in our everyday lives- the moral issues of friendship, family, emotions, character, the limits of tolerance and honesty, and the strength of our values.